2022
DOI: 10.1039/d2fo02479a
|View full text |Cite
|
Sign up to set email alerts
|

Citrus flavanone metabolites protect pancreatic β-cells against cholesterol stress through a multi-proteomic mechanism

Abstract: Citrus flavanones may improve oxidative stress and insulin resistance induced by western diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…59 NF-κB1 is a member of the NF-κB family which plays an important role in cell function and inflammation. Fraga et al 22 also found NF-κB1 significantly enriched after treatment of pancreatic β-cells in high concentrations of cholesterol with H7G, evidencing the hesperidin-mediated protection of pancreatic β-cells from apoptosis. This analysis suggests that OJ consumption could modulate the expression of plasma TFs that play a crucial role in reducing risks of CVD and other metabolic disorders.…”
Section: Papermentioning
confidence: 90%
See 2 more Smart Citations
“…59 NF-κB1 is a member of the NF-κB family which plays an important role in cell function and inflammation. Fraga et al 22 also found NF-κB1 significantly enriched after treatment of pancreatic β-cells in high concentrations of cholesterol with H7G, evidencing the hesperidin-mediated protection of pancreatic β-cells from apoptosis. This analysis suggests that OJ consumption could modulate the expression of plasma TFs that play a crucial role in reducing risks of CVD and other metabolic disorders.…”
Section: Papermentioning
confidence: 90%
“…48,49 Considering that flavanone and carotenoid metabolites can modulate the expression of large numbers of genes to exert their biological effects, we performed an untargeted proteomic analysis and observed, for the first time, OJ exerting important modifications on the plasma proteome. Although the effects of OJ consumption have been previously reported in PBMC 21 and pancreatic β-cells, 22,23 studies have not yet assessed the plasma proteome.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation